Entrepreneurship of Islamic Business Management Students in Post-Graduation Business Practices - Muhammad Ardiansyah; Léo-Paul Dana; Vanessa Raten (Involvement International Journal of Business, 2024)
This study explores the entrepreneurship trends among Islamic business management students upon graduating, focusing on their integration of Islamic principles into business practices. Qualitative interviews were conducted with recent graduates to investigate their entrepreneurial intentions, challenges faced, and the influence of their educational background on business decisions. Findings indicate a strong inclination among graduates towards entrepreneurship, driven by a desire to align business ventures with Islamic ethical values. They encounter significant challenges such as accessing Sharia-compliant financing, navigating regulatory frameworks, and establishing networks within the Islamic business ecosystem. Graduates leverage their educational experiences, which combine practical entrepreneurial skills with Islamic business ethics, to navigate these challenges. Mentorship and supportive networks play pivotal roles in their entrepreneurial journey, providing guidance in both conventional business practices and Islamic finance intricacies. Opportunities within the Islamic economy, including halal products and ethical investments, are identified as key markets for entrepreneurial endeavors. Islamic business management graduates demonstrate a proactive stance towards entrepreneurship, integrating Islamic principles into their business models while navigating complex challenges. Educational programs that blend Islamic ethics with entrepreneurial skills are crucial in preparing graduates for sustainable ventures within the Islamic economy, emphasizing the need for ongoing support and adaptation in a dynamic market environment.